2017
DOI: 10.1186/s12871-017-0329-z
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension attenuates the dynamic preload indicators increase during experimental hypovolemia

Abstract: BackgroundPulse pressure (PPV) and stroke volume (SVV) variations may not be reliable in the setting of pulmonary hypertension and/or right ventricular (RV) failure. We hypothesized that RV afterload increase attenuates SVV and PPV during hypovolemia in a rabbit model of pulmonary embolism (PE) secondary to RV dysfunction.MethodsSeven anesthetized and mechanically ventilated rabbits were studied during four experimental conditions: normovolemia, blood withdrawal, pulmonary embolism and fluid loading of a collo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…In this setting, intravascular volume dehydration should be needed to avoid exacerbating bi-ventricular cardiac dysfunction because of less chance of improvement on RV contractility over a wide range of filling pressures due to flatter Starling curve of RV than the LV [ 43 ]. This may lead to RV global dysfunction and secondarily with LV systolic dysfunction, making the animals none or less responsive to fluid loading [ 44 ], as demonstrated in the Control group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this setting, intravascular volume dehydration should be needed to avoid exacerbating bi-ventricular cardiac dysfunction because of less chance of improvement on RV contractility over a wide range of filling pressures due to flatter Starling curve of RV than the LV [ 43 ]. This may lead to RV global dysfunction and secondarily with LV systolic dysfunction, making the animals none or less responsive to fluid loading [ 44 ], as demonstrated in the Control group.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this study was carried out before and after abdominal wall closure for ethical aspects of veterinary patients’ safety. While previous studies have suggested that dynamic preload indicators such as PPV and SVV are able to predict fluid responsiveness during major abdominal surgery [ 60 , 61 ], there are still some controversies regarding the predictive values of fluid responsiveness compared to values obtained in the ICU setting [ 44 ]. Future studies are expected to establish the utility of EV-based goal-directed therapy in larger populations to ensure adequate hemodynamic stabilities throughout the phase of surgical anesthesia and improved outcomes of the emergency canine patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the presence of RV failure should be suspected when a patient has significant variations of stroke volume or pulse pressure but does not respond to fluids [ 73 ]. However, the performance of the stroke volume variation and pulse pressure variation could depend on the volume status: during normovolemia their high values failed to predict volume responsiveness (false positive) [ 74 ]; by contrast, during hypovolemia their normal values predict volume unresponsiveness (true negative), avoiding dangerous fluid loading [ 75 ].…”
Section: Treatmentmentioning
confidence: 99%
“…The current study has several limitations. Pulmonary hypertension and right ventricular dysfunction can mask hypovolemia and normalize the values of dynamic preload indices 27 . We discarded a significant increase in pulmonary pressure by PHE administration since ∆SV EEOT and ∆AoF EEOT remained elevated after BW.…”
Section: Discussionmentioning
confidence: 99%